Woman Leadership in Toba Batak Society a Critical Study on Patriarchy - Naibaho, Megawati; Manik, Resmin; Sipahutar, Antonius P; Sihite, Bartolomeus; Marbun, Martina Rosmaulina (Universitas Sanata Dharma, 2024)
This research is an attempt to highlight the important aspect that leads to the inequality and marginalization of women in Toba Batak society, including their exclusion from leadership roles. The women experience this marginalization rationalized by the patriarchal system which is persistent and enduring even to this day. The role of the patriarchy system has resulted gender-inequality system that subordinate women in Toba Batak society. The Toba Batak patriarchal system is implemented in all aspects of life such as myths, rituals, organizations, leadership, and kinship systems. The cultural beliefs and rituals have created an attitude among the Toba Batak to view men as first class and women as second class. The research used qualitative research method particularly through ethnography. The researchers belong to the Toba Batak community attempt to be neutral and professionally on observing the life practices of the Toba Batak community. This research uses Pierre Bourdieu's theory of practice, especially doxa to analyze critically the Toba Batak, regarding leadership roles. Furthermore, this research includes the critique of patriarchy by Elisabeth Schüssler Fiorenza and Mary John Mananzan who have engaged with Bourdieu on how to approach the struggle against patriarchy. This research aims to reach the root causes of discrimination on leadership especially the women exclusion. Finally, the researchers offer pastoral invitation the importance equality between men and women as the image of God through family formation.